Pengaruh Desain Kemasan, Kualitas Produk, dan Electronic Word of Mouth (E-WOM) Terhadap Loyalitas Konsumen Melalui Kepuasan Pelanggan sebagai Variabel Mediasi pada Produk Air Minum Marina - Muhammad Fadril Sanggili; Samsudin Samsudin; Asmawati Asmawati (Journal of Management and Creative Business, 2026)
This study aims to analyze the influence of packaging design, product quality, and Electronic Word of Mouth (E-WOM) on consumer loyalty through customer satisfaction as a mediating variable for Marina bottled water products. An explanatory quantitative approach was used, involving 97 respondents in Dompu District who were selected through purposive sampling. Data collection was conducted using a Likert-scale questionnaire and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 3. The results of the study indicate that packaging design has a positive and significant effect on consumer loyalty, both directly and indirectly through customer satisfaction. Product quality was found to have a significant effect on customer satisfaction and is capable of building loyalty indirectly through the mediating effect of satisfaction, although it does not have a direct effect. Conversely, E-WOM has absolutely no effect on either customer satisfaction or loyalty, either directly or indirectly. Finally, customer satisfaction was found to have a very strong, positive, and significant influence on directly shaping consumer loyalty toward Marina bottled water. This study confirms that customer satisfaction serves as a crucial mediating bridge for transforming a product’s physical attributes into long-term brand loyalty for daily-use products.